Strategic Planning of IS/IT With Ward and Peppard Approach - Setiawan, Decka Alifando; Eko Wulandari, Sri Hariani; Maulana, Yoppy Mirza (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2018)
PT. Bumi Samudera Jaya is one of many shipbuilding sub-contractor in Indonesia. To achieve the competitive advantage for bringing the best service for its client, the company needs a solution to formulate the IS/IT strategic plan. There are implications if the company don’t implement the IS/IT strategic planning such as IS/IT investation, information distribution, IS/IT human resource development, monitoring function and no IS/IT prioritization in the company. To overcome those problems, company needs to implement the strategic planning to plan the IS/IT implementation with Ward & Peppard approach and formulate the business IS strategy, IT strategy, IS/IT management strategy, application portofolio and application portfolio roadmap. The results of this research are 28 IS/IT solutions. IT strategy with output such as network architecture, hardware & software, platform and database. IS/IT management strategy with IS/IT human resource structure. Application portfolio with 7 solutions in strategic quadrant, 9 solutions in key operational quadrant, 10 solutions in support quadrant and 2 solutions in high potential quadrant. Application portfolio roadmap with 5 batch of category based on value chain stream which plotted in term of 5 years of implementation from last year of 2018 until year 2023, the detail of IS/IT funding and urgency assessment based on risk calculation for every IS/IT solution.